Genetic and environmental factors that affect the best time of Thoroughbred horses in Brazil - Mota, MDS; Oliveira, H. N.; Silva, R. G. (Blackwell Wissenschafts Verlag Gmbh, 1998)
On the basis of information provided by the Brazilian Association of Race Horse Breeders, we analysed the racing performance of 947 Thoroughbred horses in races held from 1985 to 1992. The performance was evaluated using the best, time of the animals. The variance component was obtained by the derivative-free restricted maximum likelihood method, and the model used contained fixed effects of the racing month and year, sex, race track, track condition, animal age, number of competitors in race, and distance, and the random animal effect. The low heritability estimate obtained (0.12) indicates that selection based on animal phenotypic value must induce small genetic changes in this trail.